2020
DOI: 10.1111/1440-1681.13260
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal taurine exerts a hypotensive effect in male spontaneously hypertensive rats and down‐regulates endothelial oxide nitric synthase in the aortic arch

Abstract: Essential hypertension is considered to be a result of the interaction between genetic and environmental factors, including perinatal factors. Different advantageous perinatal factors proved to have beneficial long‐lasting effects against an abnormal genetic background. Taurine is a ubiquitous sulphur‐containing amino acid present in foods such as seafood. The antihypertensive effects of taurine have been reported in experimental studies and in human hypertension. We aimed to investigate the effects of perinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
(133 reference statements)
0
5
0
Order By: Relevance
“…Consistent with the latter, we confirmed that chronic ingestion of ED markedly reduced blood pressures, consistent with our previous findings ( 17 ). Whilst caffeine is widely recognized to raise blood pressure, taurine has marked acute and chronic hypotensive effects ( 35 37 ). Ishikawa et al showed that drug-induced hypotension in dogs resulted in BBB dysfunction ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the latter, we confirmed that chronic ingestion of ED markedly reduced blood pressures, consistent with our previous findings ( 17 ). Whilst caffeine is widely recognized to raise blood pressure, taurine has marked acute and chronic hypotensive effects ( 35 37 ). Ishikawa et al showed that drug-induced hypotension in dogs resulted in BBB dysfunction ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Reprogramming effects have been observed through amino-acid-targeted therapies in rats ranging from 4 weeks to 50 weeks old, coarsely equivalent to human ages spanning from young children to middle adulthood [139]. Amino acid supplementation utilized as reprogramming interventions includes arginine [116], citrulline [62,[117][118][119][120][121], taurine [122][123][124][125][126][127][128][129], cysteine [130][131][132][133][134], glycine [135], BCAAs [136,137], and tryptophan [138]. The subsequent sections will delve into each of these aspects in detail.…”
Section: Effects Of Perinatal Amino Acid Supplementation On Offspring...mentioning
confidence: 99%
“…The table illustrates that maternal taurine supplementation provides protection against hypertension programmed by maternal high-sugar intake [124], maternal CKD [125], STZ-induced diabetes [126], or maternal dyslipidemia [127]. Furthermore, perinatal taurine supplementation has demonstrated efficacy in preventing hypertension in SHRs and stroke-prone spontaneously hypertensive rats (SHRSP) [128,129]. In addition, maternal taurine supplementation can ameliorate obesity programmed by a maternal high-fat/high-fructose diet [122] and maternal dyslipidemia [127].…”
Section: Taurinementioning
confidence: 99%
“…Conversely, certain amino acids can be used as reprogramming interventions to reverse the early-life insults induced by programmed processes and can consequently protect offspring against adverse outcomes. In the current review, we only focus on amino acid supplementation starting during pregnancy as a reprogramming strategy to prevent hypertension of developmental origin in rodent animal models, as listed in Table 2 [ 52 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 ]. This list is by no means complete and is likely to grow quickly, as the study of DOHaD-related disorders is a flourishing field.…”
Section: Insight From Animal Models Targeting Amino Acids To Prevementioning
confidence: 99%
“…Table 2 shows that combined use of taurine and arginine in the perinatal period causes a reduction of BP in SHRs as well as in FHH rats [ 88 , 89 , 90 , 91 ]. Perinatal taurine supplementation alone has also been shown to prevent hypertension in SHRs and stroke-prone spontaneously hypertensive rats (SHRSP) [ 94 , 95 ]. Additionally, maternal taurine supplementation protects adult offspring against hypertension programmed by maternal high-sugar intake or diabetes [ 92 , 93 ].…”
Section: Insight From Animal Models Targeting Amino Acids To Prevementioning
confidence: 99%